87.2k views
0 votes
3(x + 4) + 2 = 2 + 5(x – 4) what is the third step in solving this equation>

A.combine like terms
B.distributive property
C.division property of equality
D.subtraction property of equality

2 Answers

6 votes
The third step is D. subtraction property of equality

Simplify both sides of the equation.

3(x+4)+2=2+5(x−4)

Simplify

3x+14=5x−18

Subtract 5x from both sides.

3x+14−5x=5x−18−5x

−2x+14=−18

Subtract 14 from both sides. <---- Step 3

−2x+14−14=−18−14

−2x=−32

Divide both sides by -2.

−2x/−2 = −32/−2

x=16
User Harsh Makani
by
6.4k points
6 votes
The answer is B from my understanding

User Mittenchops
by
5.6k points